你可能感兴趣的试题
X1 X2
(Xl,X2) (Xl,X2,X3,X4)
2x+3y=5xy 5x2·x3=5x5 4x8÷2x2=2x4 (-x3)2=x5
4xy+xy=5xy x+2x=2x² 5xy-3xy=2 x+y=xy
3x+4y=7xy 6y2-y2=5 b4+b3=b7 4x-x=3x
(x2)3=xy3 (xy)3=x3y3, 4x3y÷x=4x2y(x≠0) x2+x2=x4
X1 X2 (X1,X2) (X1,X2,X3,X4)
4-x2+3x=(2-x)(2+x)+3x -x2+3x+4=-(x+4)(x-1) 1-4x+4x2=(1-2x)2 x2y-xy+x3y=x(xy-y+x2y)
(x-y)2=x2-y2 x2·y2 =(xy)4 x2y+xy2 =x3y3 x6÷y2 =x4
X1 X2 (X1,X2) (X1,X2,X3,X4)
X1 X2 (X1,X2) (X1,X2,X3,X4)
(-2x2)3=-6x6 x4÷x2=x2 2x+2y=4xy (y+x)(-y+x)=y2-x2
2x+2y=2xy (x2y3)2=x4y5 (xy)2÷![](http://static.xtika.com/tiku_img/106112/Picture/9f1ba94a8828e448.jpg)
=(xy)3 2xy﹣3yx=xy
(4xy2)2=8x2y4 3x2=9x2 (﹣x)7÷(﹣x)2=﹣x5 (6xy2)2÷2xy=3xy3
x﹣2x=﹣x 2x﹣y=xy x2+x2=x4 (x﹣l)2=x2﹣1
X1 X2 (Xl,X2) (Xl,X2,X3,X4)
-x2-y2 = -(x+y)(x-y) x2y+2xy+4y = y(x+2)2 -49x2+x2y2 = (xy+7x)(xy-7x) 16x2+4y2-16xy = 4(2x-y)2